Research Progress on the Development of Porcine Reproductive and Respiratory Syndrome Vaccines - Hang Zhang; Qin Luo; Yingxin He; Yajie Zheng; Huiyang Sha; Gan Li; Weili Kong; Jiedan Liao; Mengmeng Zhao (Veterinary Sciences, 2023)
Porcine reproductive and respiratory syndrome (PRRS) is a highly contagious disease in the pig industry, but its pathogenesis is not yet fully understood. The disease is caused by the PRRS virus (PRRSV), which primarily infects porcine alveolar macrophages and disrupts the immune system. Unfortunately, there is no specific drug to cure PRRS, so vaccination is crucial for controlling the disease. There are various types of single and combined vaccines available, including live, inactivated, subunit, DNA, and vector vaccines. Among them, live vaccines provide better protection, but cross-protection is weak. Inactivated vaccines are safe but have poor immune efficacy. Subunit vaccines can be used in the third trimester of pregnancy, and DNA vaccines can enhance the protective effect of live vaccines. However, vector vaccines only confer partial protection and have not been widely used in practice. A PRRS vaccine that meets new-generation international standards is still needed. This manuscript provides a comprehensive review of the advantages, disadvantages, and applicability of live-attenuated, inactivated, subunit, live vector, DNA, gene-deletion, synthetic peptide, virus-like particle, and other types of vaccines for the prevention and control of PRRS. The aim is to provide a theoretical basis for vaccine research and development.